The Effect of Graphite Concentration in TiO2 Semiconductors on Efficiency of Dye Sensitized Solar Cells (DSSC) Using Dye Melastoma malabathricum L Fruit Extract - Riski Gusti, Diah; Mastutik, Diah; Lestari, Intan; Walidatur Rofiah, Yuliana (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
The effect of graphite mass in TiO2 semiconductors on the efficiency of Dye-Sensitized Solar Cell (DSSC) based on dye extract of Melastoma malabathricum has been investigated. This study aims to determine the effect of mass variations of graphite-TiO2 on the efficiency of DSSC and bandgap produced in the manufacture of DSSC. The mass variation of graphite added in TiO2 semiconductors is 10%, 12%, 14%, and 16% of the mass of TiO2. The result shows the maximum wavelength (Î»max) for anthocyanin at 544 nm with an absorbance of 5.7 Ã. The calculation results obtained by the optimal bandgap value in the variation of graphite mass 14% is 3.15 eV. The results of characterization using XRD obtained tetragonal TiO2 crystal structure with a particle size of 49.8 nm. The DSSC test results obtained optimal results found in mass variations of 14% graphite with a current strength of 140,001 Î¼A, a voltage of 1446.9 mV, and DSSC efficiency of 0.2026%.